2017
DOI: 10.1155/2017/3456264
|View full text |Cite
|
Sign up to set email alerts
|

Status of Epstein-Barr Virus Coinfection withHelicobacter pyloriin Gastric Cancer

Abstract: Epstein-Barr virus is a ubiquitous human herpesvirus whose primary infection causes mononucleosis, Burkett's lymphoma, nasopharyngeal carcinoma, autoimmune diseases, and gastric cancer (GC). The persistent infection causes malignancies in lymph and epithelial cells. Helicobacter pylori causes gastritis in human with chronic inflammation. This chronic inflammation is thought to be the cause of genomic instability. About 45%-word population have a probability of having both pathogens, namely, H. pylori and EBV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 269 publications
0
39
2
3
Order By: Relevance
“…Certain co-infections could also increase one’s risk, such as HIV and H pylori [1]. Kayamba et al reported EBVaGC among 60% of HIV patients in Zambia, suggesting HIV increases risk for EBV related gastric cancers [47].…”
Section: Epidemiology Of Ebvagcmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain co-infections could also increase one’s risk, such as HIV and H pylori [1]. Kayamba et al reported EBVaGC among 60% of HIV patients in Zambia, suggesting HIV increases risk for EBV related gastric cancers [47].…”
Section: Epidemiology Of Ebvagcmentioning
confidence: 99%
“…Until the late 1930s, gastric cancer was the leading cause of cancer death in the United States [1]. Today, it is the third most common cause of cancer-related mortality and the fifth most common cancer worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recientemente se describe que VEB puede en asociación con el Helicobacter pylori generar un sinergismo en la carcinogénesis de esta entidad 22 .…”
Section: Epstein Barr Virusunclassified
“…Lipopolysaccharide (LPS) binds to external receptors and activates cellular signal pathways, promoting the occurrence and development of GC [6]. In addition, EBV infection can also promote development of GC [7,8]. Therefore, GC is considered an inflammation-related cancer [2,9].…”
Section: Introductionmentioning
confidence: 99%